Implantation with SHED sheet induced with homogenate protein of spinal cord promotes functional recovery from spinal cord injury in rats - Mi, Sisi; Wang, Xue; Gao, Jiaxin; Liu, Yu; Qi, Zhongquan (Frontiers in Bioengineering and Biotechnology, 2023)
After SCI occurs, the lesion is in a growth inhibitory microenvironment that severely hinders neural regeneration. In this microenvironment, inhibitory factors are predominant and factors that promote nerve regeneration are few. Improving neurotrophic factors in the microenvironment is the key to treating SCI. In this study, we designed a bioactive material with a spinal cord-like structure - SHED sheet induced with homogenate protein of spinal cord (hp-SHED sheet). Hp-SHED sheet maximally mimics the microenvironment of the developing spinal cord and facilitate cell survival, proliferation and differentiation. Hp-SHED sheet also acts as a natural and stable structure for the sustained release of neurotrophins. The sustained action of neurotrophins improves the pathological microenvironment, which effectively promots neuronal regeneration, axonal extension, and inhibits glial scarring at the spinal cord lesion, thereby promoting the in situ centralis neuroplasticity. Applying hp-SHED sheet to a rat model of SCI, the recovery of sensory and motor functions has significant efficacy. Thus, hp-SHED sheet therapy is a promising strategy for effective treatment of SCI based on neurotrophins delivery.